High-temperature polymer electrolyte membranes: Proton conductivity and performance of polybenzimidazole/Ti0.9Mn0.1P2O7 - Mishra J.N.; Devi N.; Chen Y.-S.; Sharma M.; Singh P. (My University, 2025)
Polymer electrolyte membranes have proven to be highly successful in creating efficient, emission-free fuel cells, but their low-temperature limitation restricts full potential utilization. To address this issue, in the present work, polybenzimidazole (PBI)/Ti0.9Mn0.1P2O7 (TMP) inorganic-organic composite membranes were fabricated, and their morphological and structural characterizations were performed. Before testing, all membranes were loaded with phosphoric acid. The resulting PBI/TMP composite membrane has a higher proton conductivity of 212.3 mS cm−1 and activation energy ⁓ 5.49 kJ mol−1 as compared to the pristine PBI membrane with protonic conductivity 102.7 mS cm−1 and activation energy ⁓ 1.24 kJ mol−1. The PBI/TMP membrane can function effectively up to 180 °C, achieving a maximum peak power density of 376 mW cm−2 at the current density of 1120 mA cm−2 with the open circuit potential ⁓0.940 V. The inclusion of TMP significantly enhances overall cell performance compared to pristine PBI, where the peak power density of 364 mW cm−2 and current density of 958 mA cm−2 at 180 °C were obtained with an open circuit potential of 0.819 V. This study revealed successfully the potential of PBI/TMP composite membranes for their application in high-temperature proton exchange membrane fuel cells. © 2025 Elsevier B.V.